"Ta'wil Mukhtalaf al-Hadith" by Imam Ibn Qutaybah al-Daynuri: a methodological analytical study - Mat Jusoh, Nor Asmira; Nik Din, Nik Muniyati; Nik Din, Nik Mursyidah; Junoh, Noraini (Universiti Teknologi MARA, Kelantan, 2018)
This research primarily examines the book "Ta'wil Mukhtalaf al-Hadith" by Imam Ibn Qutaybah al-Daynuri. This book is considered one of the earliest works written in the science of Mukhtalaf al-Hadith (Conflicting Hadiths). The nature of the study is limited to examining the author's methodology in dealing with hadiths that appear to contradict one another and his method for resolving such conflicts. The study relies on an inductive research approach by reading primary sources and references related to the research topic. The study follows an analytical approach, specifically analyzing Ibn Qutaybah’s method in defending conflicting hadiths. This study begins with an introduction to Imam Ibn Qutaybah, his writings, the science of Mukhtalaf al-Hadith and its issues, and the author's methodology in presenting the book's contents. Among the most important findings reached by the study is that Imam Ibn Qutaybah was a man of letters (Adib), a jurist (Faqih), a historian, and a hadith scholar (Muhaddith). His book is considered one of the important references in the science of Mukhtalaf al-Hadith, specifically in refuting claims that there are contradictions between the hadiths of the Prophet (peace be upon him).